2018
DOI: 10.4155/fsoa-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Bioinformatics Analyses of Differential Circular RNA Expression in Prostate Cancer Cells

Abstract: Aim:There is little knowledge about the expression profile and function of circular RNAs (circRNAs) in prostate cancer (PCa).Methods:The expression profiles of circRNAs in RWPE-1, 22RV1 and PC3 cells were explored via high-throughput circRNAs sequencing and validated by real-time qPCR. The roles of differentially expressed circRNAs were evaluated by bioinformatics analyses.Results:Altogether 9545 circRNAs were identified and hundreds of differentially expressed circRNAs were recognized. CircRNA–miRNA networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…CircRNA-miRNA mapping has revealed that studying the interaction between circRNAs and miRNAs may further help to characterize the role of certain circRNAs in PCa development. In vitro investigations of interactions such as CDR1as-miR-7[ 66 ], circRNA-MYLK- miR-29a[ 64 ], and circBAGE2-miR-103a[ 66 ] have implicated tumor suppressive and oncogenic roles of circRNAs, which could imply their utility as biomarkers as well as therapeutic targets[ 64 ]. Other studies have shown that some circRNAs may play roles in contributing to therapy-resistance PCa.…”
Section: Circular Rna In Prostate Cancermentioning
confidence: 99%
“…CircRNA-miRNA mapping has revealed that studying the interaction between circRNAs and miRNAs may further help to characterize the role of certain circRNAs in PCa development. In vitro investigations of interactions such as CDR1as-miR-7[ 66 ], circRNA-MYLK- miR-29a[ 64 ], and circBAGE2-miR-103a[ 66 ] have implicated tumor suppressive and oncogenic roles of circRNAs, which could imply their utility as biomarkers as well as therapeutic targets[ 64 ]. Other studies have shown that some circRNAs may play roles in contributing to therapy-resistance PCa.…”
Section: Circular Rna In Prostate Cancermentioning
confidence: 99%
“…Thus, the relationship between the circRNA and the lncRNA transcript was of particular interest. In this circRNA panel, two additional circRNAs from the genes CSNK1G3 and GUCY1A2 were included as these circRNAs were recently identified in PCa tissue samples and PCa cell lines as mentioned in the introduction [ 44 , 45 ]. Collectively, the microarray analysis of the six paired samples in the discovery phase ( Figure 1 ) must be considered an exploratory study for ranking deregulated circRNAs using the unadjusted p -values supported by the mentioned additional selection criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Circ CSNK1G3 , for example, seems to promote cell proliferation in PCa [ 44 ]. Furthermore, Zhang et al [ 45 ] applied a bioinformatics approach using various PCa cells to identify numerous circRNAs, including circ GUCY1A2 , as potential candidates for PCa progression. Other working groups using microarray platforms have reported lists of the top up- and downregulated circRNAs in PCa tissue compared with adjacent normal tissue [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…They ranked in the top 3% and were associated with liver cancer. For prostate cancer (DOID: 10283), hsa_circ_0001946 (Zhang et al, 2018) and hsa_circ_0001649 (Yi et al, 2016) ranked 3rd and 5th in the ranking, respectively. They were documented to be related to prostate cancer.…”
Section: Resultsmentioning
confidence: 99%